Общие итоги раскопок городища Китей в 2004-2006 гг. - Молев, Е.А. (Боспорские исследования, 2009)
In 2004, the expedition of Nizhny Novgorod state University named by N.I.Lobachevsky together with the Kerch Historical and Cultural Reserve recommenced research of the Bosporus city of Kytaia located 40 km to the south from the modern city of Kerch owing to the grant of «Cimmerida» foundation (Moscow). In the period between 2004 and 2006 a new geodetic survey of the city site was made. Excavations on the eastern side of the burn mound in its central part were made. Judging by archaeological resources of the previous years the cult centre of the city was situated here. As a result of the work the complex of late ancient buildings in the eastern outskirts of the burnt mound was discovered. They are evidence of pagan rites being in existence in spite of dissemination of Christianity in the Bosporus since the 4th century AD. It also proves the cult centre of the city was keeping its significance right up to its fall in the 6th century AD. In 2004, the expedition of Nizhny Novgorod state University named by N.I.Lobachevsky together with the Kerch Historical and Cultural Reserve recommenced research of the Bosporus city of Kytaia located 40 km to the south from the modern city of Kerch owing to the grant of «Cimmerida» foundation (Moscow). In the period between 2004 and 2006 a new geodetic survey of the city site was made. Excavations on the eastern side of the burn mound in its central part were made. Judging by archaeological resources of the previous years the cult centre of the city was situated here. As a result of the work the complex of late ancient buildings in the eastern outskirts of the burnt mound was discovered. They are evidence of pagan rites being in existence in spite of dissemination of Christianity in the Bosporus since the 4th century AD. It also proves the cult centre of the city was keeping its significance right up to its fall in the 6th century AD.